Antecedentes en la investigación sociodemográfica sobre las separaciones conyugales en Latinoamérica, 1980-2017 - Ruiz-Vallejo, Fernando; Solsona i Pairó, Montserrat (El Colegio de México A.C., 2020)
The aim of this article is to systematize the sociodemographic literature on union dissolution in Latin America between 1980 and 2017 through, on the one hand, the identification of methodologies and sources used for their study, and another, the documentation of its differentials. The results allow proposing three narrations underlying the evolution of this topic: a) the works that analyze the union dissolution as an inhibitor and / or promoter of fertility; b) those who conceive it as an expression of modernization in the framework of the second demographic transition; and c) those who conceive it as an object of study itself.